Trade-Offs in Marine Policy Decisions Through the Lens of Literature - Joyce Dias Gois Rodrigues de Queiroz; Débora Gutierrez; Helena Maria Gregório Pina Calado (Oceans)
The ocean is increasingly affected by the rise in maritime activities. Increased anthropogenic pressures have led to environmental impacts and also intensified competition for space and resources among various socioeconomic sectors. To mitigate these impacts on marine ecosystems and reduce conflicts, management tools and processes such as marine protected areas (MPAs) and maritime spatial planning (MSP) have become more prevalent. Trade-offs are inherent to these, and necessary to meet specific conservation and socioeconomic goals. In response, understanding and managing these trade-offs has become crucial to achieving ocean sustainability. This study performs a bibliometric review to identify the types of trade-offs discussed in the marine literature and examines their operationalization for the conservation and sustainable use of marine resources. The analysis reveals that trade-offs, particularly those between conservation and development, and the interests of specific stakeholders, are most frequently addressed in the trade-off literature and are typically approached through integrative methods. This comprehensive examination highlights the significance of recognizing and addressing trade-offs to achieve effective marine management and conservation, aligning ecological integrity with socioeconomic interests.